The Role of Religious and Secular Dynamics in Shaping Pakistani National Identity: Challenges and Opportunities - Shabbir, Ghulam; Ali, Sharaf; Jawad, Khizar (Annals of Human and Social Sciences, 2024)
This study explores the complex interplay between religious and secular dynamics in shaping Pakistani national identity, addressing both challenges and opportunities. Historically, Pakistan was founded with an Islamic ideological underpinning, yet envisioned by some leaders as a secular state. This duality has influenced national identity formation. Utilizing a mixed-methods approach, data were collected from primary and secondary sources, especially, analysis of historical documents, policy papers and academic works. The findings reveal that state-sponsored religious policies and the influence of religious political groups have significantly shaped national identity, often leading to societal divisions. Conversely, secular movements, although facing resistance, have played a critical role in advocating for a more inclusive identity. The study recommends a balanced policy approach that integrates both religious and secular perspectives, educational reforms to promote inclusivity, and media initiatives to foster dialogue. Civil society’s role in encouraging interfaith and intercultural understanding is also emphasized as crucial for national unity.